COPING WITH AND MANAGING STRESS STYLES OF FRESHMEN PHYSICAL EDUCATION STUDENTS AT THE PE FACULTY IN NIS - Danica Pirsl (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Stress is frequently viewed as an enemy. This is a misconception. Stress is often neither positive nor negative. Selye referred to stress judged as "good" as eustress. Distress, on the other hand, is stress that results in negative responses. Unchecked negative stress can interfere with the physiological and psychological functioning of the body and may ultimately result in disease or disability. A stressor is any physical, psychological or environmental event, or condition that initiates the stress. The body responds with the same threestage process. This series of changes is known as the general adaptation syndrome (GAS). The three phases are alarm, resistance, and exhaustion. It is interesting to note that PE students form their own stress copying styles in the mental, emotional and physical areas. Results are enhanced activities, sense of control and high energy level. Both male and female students show similar patterns of behaviour in stressful situations but female students show more interest in sporting activities when in stress-related situation